The Triad of State, Law, and Religious Failure in Protecting Children's Rights After Divorce: An Empirical Legal Study in Urban Communities in Pekanbaru - Tiara Nurafifa; Muhammad Hafis; Jumni Nelli; Juliani Syafitri (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Based on data from the Central Statistics Agency in 2023, one in three children no longer receive their basic rights after their parents' divorce. In Delima District, Pekanbaru—which has the highest divorce rate in Riau Province at 18.5%—72% of mothers reported difficulty in financing their children's education, while 45% of children experienced emotional disturbances. Therefore, this article aims to examine the reality of children's rights after divorce in the urban area of Pekanbaru, focusing on the following questions: Why are children's rights (especially alimony and education) in urban areas such as Pekanbaru often neglected after divorce? What systemic failures hinder this? And what is the social reality when it comes to fulfilling children's rights? Using a qualitative-phenomenological approach through descriptive case studies, this research involved six main informants, plus two religious affairs officials and two religious leaders who were selected purposively. Data were collected through in-depth interviews and analyzed using thematic analysis techniques. The results show that the neglect of children's rights after divorce in Pekanbaru (especially in the Delima subdistrict) is caused by a triadic failure: the state (absence of a safety net for children who are victims of divorce), the law (inconsistency in alimony regulations, weak enforcement of court decisions, high litigation costs), and religious institutions (failure to encourage fathers to fulfill their responsibilities in accordance with Islamic mandates). This failure also reflects the weak enforcement of Islamic family law principles, particularly in the implementation of hadhanah and nafkah obligations as stipulated in the KHI and the Marriage Law, which have not been able to guarantee comprehensive protection for children. This is compounded by the persistent patriarchal culture that makes ex-wives reluctant to fight for their children's rights. These findings call for policy reform based on an integrated child rights framework that bridges formal law, religious values, and community mechanisms, as well as the deconstruction of patriarchal culture in the enforcement of children's rights.